Chapter Rubinrote Federn, Walzähne und schimmerndes Perlmutt: polynesische Kosmologie in Ritualobjekten - Wilhelmina Haslwanter, Katharina (Scheidegger & Spiess, 2014)
This article is concerned with cosmological concepts of the peoples of Polynesia in the Pacific. Following a creation myth from Tahiti, the authors explore the realms of te ao (the world of space and light which came to be inhabited by humans) and te po (the engulfing darkness, associated with the night, the ancestors and spirits) by investigating artefacts from the region. Certain qualities of the rare materials used in the highly skilled making, and the knowledge of the utilisation of these artefacts enabled pacific islanders to establish a connection to divine entities but also to protect themselves of their powers. Many of the cosmological principles finally can be rediscovered in the objects themselves, which therefore are a study of the cosmos in miniature.